Fostering Conceptual Roles for Change: Identity and Agency in Esea Teacher Preparation - Morgan, Brian (Archīum Ateneo, 2024)
English Changing, the theme and title of the 2009 ESEA conference held in Manila, raises specific challenges for language teacher education: To what extent do we prepare teachers to be passive recipients of the social, cultural, and economic changes that align with the global spread of English? Alternatively, how might we encourage teachers to become active participants—“agents of change”—through their mediation and implementation of language curricula and pedagogy? The author addresses such questions by first reflecting on his own personal and professional development in EFL and EAP teaching contexts. These experiences are then related to the growing research literature in language teacher identity and several theoretical issues related to this area of interest. The following sections of the article look at the complexities of transferring theory to practice in the specific context of a pre-service, language teacher education course, one of whose primary goals is to foster awareness of language as a social practice linked to unequal relations of power, and one in which language teachers are encouraged to imagine and act otherwise through their teaching and interpersonal relationships with students and colleagues. In the final sections, these course aspirations are explored through a group assignment called a “social issues project,” in which students conceptualize and design a blueprint for transformative action in various forms such as an advocacy letter, workshop, curricular materials, etc. Reflection on the strengths and weaknesses of several selected projects, and how they relate with ESEA issues, conclude the article.